A CONTEXTUAL APPROACH TO GEOGRAPHY LEARNING IN SCHOOL - Puastuti, Dwi; Sinthiya, Ida Ayu Putu Anggie (JLCEdu (Journal of Learning and Character Education), 2021)
This study aims to find out how to apply a contextual approach to geography learning in schools. This research is qualitative research with descriptive analysis technique with literature study. This literature study aims to determine how contextual learning is applied in learning geography in schools. The author collects data and information related to the contextual approach in geography learning, sourced from research journals, both national and international, supporting books, newspapers, and magazines. Based on the results of the discussion in this literature study, it can be concluded that the contextual approach is very suitable to be applied in geography learning because geography learning is possible to be designed with contextual learning. After all, it deals with various physical and social phenomena around the student's environment. In its application, the contextual approach includes seven components such as constructivism, questioning, inquiry, learning community, modelling, reflection, and authentic assessment. There are several benefits of applying a contextual approach in geography learning. It can increase learning motivation, student understanding, critical thinking skills, and learning outcomes.